Who influences nutrition policy space using international trade and investment agreements? A global stakeholder analysis - Kelly Garton; Boyd Swinburn; Anne Marie Thow (BMC, 2021)
Abstract Background Regulation of food environments is needed to address the global challenge of poor nutrition, yet policy inertia has been a problem. A common argument against regulation is potential conflict with binding commitments under international trade and investment agreements (TIAs). This study aimed to identify which actors and institutions, in different contexts, influence how TIAs are used to constrain policy space for improving food environments, and to describe their core beliefs, interests, resources and strategies, with the objective of informing strategic global action to preserve nutrition policy space. Methods We conducted a global stakeholder analysis applying the Advocacy Coalition Framework, based on existing academic literature and key informant interviews with international experts in trade and investment law and public health nutrition policy. Results We identified 12 types of actors who influence policy space in the food environment policy subsystem, relevant to TIAs. These actors hold various beliefs regarding the economic policy paradigm, the nature of obesity and dietary diseases as health problems, the role of government, and the role of industry in solving the health problem. We identified two primary competing coalitions: 1) a 'public health nutrition' coalition, which is overall supportive of and actively working to enact comprehensive food environment regulation; and 2) an 'industry and economic growth' focussed coalition, which places a higher priority on deregulation and is overall not supportive of comprehensive food environment regulation. The industry and economic growth coalition appears to be dominant, based on its relative power, resources and coordination. However, the public health nutrition coalition maintains influence through individual activism, collective lobbying and government pressure (e.g. by civil society), and expert knowledge generation. Conclusions Our analysis suggests that industry and economic growth-focussed coalitions are highly capable of leveraging networks, institutional structures and ideologies to their advantage, and are a formidable source of opposition acting to constrain nutrition policy space globally, including through TIAs. Opportunities for global public health nutrition coalitions to strengthen their influence in the support of nutrition policy space include strategic evidence generation and coalition-building through broader engagement and capacity-building.